2014
DOI: 10.4028/www.scientific.net/amm.598.265
|View full text |Cite
|
Sign up to set email alerts
|

Study of Heat Rejection in Triple Natural Draft Dry Cooling Towers under Crosswind Using Radiator-Type Windbreakers

Abstract: In this paper, the effect of crosswind on triple natural draft dry cooling towers is studied and analyzed. Concerning this area, many researches have concentrated on one cooling tower. This research focuses on the mutual effects of the adjacent towers' performance, and also makes a comparison between the efficiency of the three cooling towers in windy and no-wind conditions, using Computational Fluid Dynamics (CFD). In modeling the crosswind condition, at first solid windbreakers, and then radiator-type windbr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It is concluded that compared with the radiator arranged vertically outside the tower, the heat transfer characteristics of the radiator arranged radially outside the tower are completely different from those of the radiator arranged vertically outside the tower, and the thermal hydraulic performance of the A-type frame of the heat exchanger is the most deteriorated due to the adverse effects of the environmental wind. Hozhabr et al 14,15 compared the radiator with the solid. Through numerical calculation of different windshield structures, they found that the radiator can not only improve the cooling efficiency but also reduce the wind speed compared to a fixed.…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that compared with the radiator arranged vertically outside the tower, the heat transfer characteristics of the radiator arranged radially outside the tower are completely different from those of the radiator arranged vertically outside the tower, and the thermal hydraulic performance of the A-type frame of the heat exchanger is the most deteriorated due to the adverse effects of the environmental wind. Hozhabr et al 14,15 compared the radiator with the solid. Through numerical calculation of different windshield structures, they found that the radiator can not only improve the cooling efficiency but also reduce the wind speed compared to a fixed.…”
Section: Introductionmentioning
confidence: 99%